Faculty Development Series on Graduate Medical Education: Systems-Based Practice - Sara Multerer; Michael Weisgerber; Jennifer Miller; Susan Guralnick; Sharon Dabrow; Suzette Caudle (Association of American Medical Colleges, 2016)
Abstract Introduction This module is part of a series of faculty development presentations that were commissioned by the Program Directors Committee of the American Board of Pediatrics based on its publication entitled Assessment in Graduate Medical Education: A Primer for Pediatric Program Directors. This presentation was developed with input from the primary author of the systems-based practice (SBP) chapter of that primer. This presentation is case-based and intended to involve interactive group discussion. Methods The module begins with an overview of the six ACGME core competencies, with specific attention paid to the definition of SBP, including some examples of how SBP is utilized and can be assessed in everyday practice. After the module has reviewed practical opportunities for assessment of SBP, the Pediatric Milestone Project is introduced, followed by a detailed description of the reportable milestones related to SBP and how these milestones can be used effectively in the assessment of residents. Participants are then provided with video vignettes of learners at differing levels of competence in the area of SBP and are given the opportunity to assess learners using a milestone-based evaluation tool. Results This presentation has been delivered by three of us in our respective institutions. In our experience, faculty generally find the SBP competency the most difficult to understand, and therefore evaluate, in learners. The use of the Likert scale-based evaluation tool compared to a more milestone-based tool in the presentation highlights the improved interrater reliability of using an assessment tool with more specific behavioral anchors. Faculty state they leave the presentation with a much more clear understanding of SBP and the competency's role and importance in developing resident learners. Discussion One common challenge in presenting this module is adjusting to the differing levels of faculty knowledge regarding milestones. Participants with an existing strong working knowledge of the Milestones Project, such as program directors, associate program directors, or clerkship directors, may find the information in this presentation too basic. The presentation has been most useful for participants with more limited knowledge of the milestones and assessment tools in medical education.